Austrian Liberalism in the Thought of Michel Foucault:: International Political Theory in a New Perspective - Tellez-Zepeda, Claudio A. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
In this article, I offer a conceptual clarification regarding the place occupied by central Austrian Liberal authors, Mises and Hayek, in the thought of Michel Foucault, in what concerns the gestation of the (neo)liberal biopolitics and governmentality. I also advance the argument that the study of the relationship between Foucault, Mises and Hayek opens new possibilities to think International Political Theory in late modernity as a set of reflections concerning the relationship between morality and the problem of the political in the anarchical society of sovereign nations.